STUDY ON WEAR OF TAPERED ROLLER BEARING UNDER DIFFERENT SERVICE CONDITIONS - ZHANG Yu; SHI Xiaoyu; TIAN Weisong (Jixie qiangdu)
In order to clarify the influence of different working conditions on the wear of tapered roller bearings, the wear state of tapered roller bearings was carried out.A quasi-statics model of tapered roller bearings including roller balance equation and inner ring balance equation was established, and a wear depth calculation model suitable for wear analysis of tapered roller bearings was derived based on Archard wear theory.The wear distribution characteristics of bearing inner and outer raceways and roller elements under light load, medium load and heavy load conditions were comparative analyzed.The results show that the wear depths of the tapered roller and the inner/outer raceways on the contact line show bimodal distribution characteristics, and the wear distribution of the outer raceway is closely related to the positions of the rolling elements.For light load condition, the peak wear depth of bearing raceways and roller elements increases by 20% as bearing speed increases 25%, and for heavy load condition, the peak wear depth of bearing raceways and roller elements increases more than 17% as bearing load increases 16%.The comparison of bearing wear peaks under the three working conditions shows that the product of the equivalent load and the speed of the bearing is not the determining factor controlling bearing wear，and the load change has a significant impact on the bearing wear.